2016
DOI: 10.1177/0004867416652735
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double blind, placebo-controlled trial of a fixed dose of N-acetyl cysteine in children with autistic disorder

Abstract: This study failed to demonstrate any benefit of adjunctive N-acetyl cysteine in treating autistic disorder. While this may reflect a true null result, methodological issues particularly the lower dose utilised in this study may be confounders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 23 publications
0
38
1
Order By: Relevance
“…Most of the sample population were male (633 of 765). The mean age of study participants varied considerably: four studies evaluated treatment for adults (range 18-60) [30,31,37,39], while 10 involved evaluated interventions only for children and adolescents (range 2-18) [32][33][34][35][36][38][39][40][41][42][43]. The median duration of the treatment period was 12 weeks (range 6-24).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the sample population were male (633 of 765). The mean age of study participants varied considerably: four studies evaluated treatment for adults (range 18-60) [30,31,37,39], while 10 involved evaluated interventions only for children and adolescents (range 2-18) [32][33][34][35][36][38][39][40][41][42][43]. The median duration of the treatment period was 12 weeks (range 6-24).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the 14 RCT studies found eligible, six found significant improvement as assessed by RRBs scales when comparing medication and placebo groups: two on risperidone [31,40]; one on fluvoxamine [30]; one on fluoxetine [39]; one on Buspirone [41] and, one divalproex sodium [33]. Six studies yielded negative results: one on nacetylcysteine [42]; one on oxytocin [43]; one on fluoxetine [32]; one on citalopram [36]; one levetiracetam [34]; and, one olanzapine [35]). Two studies showed a significant difference on only one of the two subscales of the RBS-R (stereotypies) of the two tools (RBS-R and Y-BOCS) used in the study: one oxytocin [31]; one N-Acetylcysteine [38] (See Table 1).…”
Section: Clinical Outcomementioning
confidence: 99%
“…In a sample size of 32 children, research showed that arbaclofen was helpful in alleviating social withdrawal and irritability. Another GABA agent, N-acetylcysteine, works by targeting the GABA pathway and decreases glutamatergic neurotransmission and has been shown to alleviate symptoms of irritability (Dean et al, 2017;Stahl, 2017).…”
Section: Gaba Agentsmentioning
confidence: 99%
“…Additionally, 2 randomized, placebo-controlled trials of NAC in conjunction with risperidone for the treatment of irritability in patients with ASD (with 50 and 40 participants, respectively) showed a significant reduction in the ABC irritability subscale score in the NAC-treated groups [184,185]. More recently, 2 other randomized, placebo-controlled trials found no benefit of NAC in children with autism [186,187].…”
Section: Supplementsmentioning
confidence: 99%